Local Wisdom as Pedagogical Capital in Islamic Education: A Critical Integrative Review from the Global South - Dyah Hapsari Eko Nugraheni; Abdullah Idi; Achmad Syarifuddin (AL-ISHLAH: Jurnal Pendidikan, 2026)
Islamic education in the Global South is embedded in local traditions, communal practices, and historically shaped power relations, yet local wisdom is often treated as cultural decoration rather than as a substantive pedagogical resource. This study examines how local wisdom is conceptualized, operationalized, and contested in the transmission of Islamic values and proposes a more contextual and ethically reflexive pedagogical framework. A critical integrative review was conducted on 32 Scopus-indexed journal articles published between 2015 and 2025. Following PRISMA-guided selection procedures, the studies were analyzed through thematic coding, conceptual clustering, and critical synthesis, with attention to pedagogical mechanisms, institutional contexts, moral authority, gender, and power relations. The findings reveal two dominant conceptualizations: local wisdom as a peripheral cultural context and as pedagogical-moral capital that shapes students’ moral habitus. Values were transmitted most effectively through role modelling, habituation, communal rituals, affective relationships, and school–community practices. However, uncritical integration may reproduce hierarchy, conformity, gender bias, exclusion, and hidden forms of authority. Institutional autonomy, curriculum flexibility, educator reflexivity, and community participation strongly influenced the depth of integration. The study concludes that local wisdom should be positioned not as symbolic local content but as a critically examined pedagogical resource. A reflexive, dialogical, and culturally responsive approach is therefore needed to strengthen ethical agency, contextual relevance, and socially just Islamic education.